Resiliensi Keuangan Keluarga Muslim dalam Menghadapi Krisis Ekonomi 2025: Pendekatan Studi Fenomenologi - Rohmatun Nafiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The global economic crisis in 2025 has had a significant impact on household financial conditions, especially among lower-middle-class communities. This study aims to describe how Muslim families in Blora Regency build and maintain their financial resilience in the face of these economic pressures. A qualitative approach using phenomenological methods was used to explore the subjective experiences of ten Muslim families. Data collection techniques were carried out through in-depth semi-structured interviews and participant observation. The results show that Muslim families' financial resilience is formed through a combination of Islamic values such as qana'ah (contentment), tawakkal (trust), and anti-riba (usury), as well as practical economic strategies such as saving, income diversification, and utilizing community-based social networks. These findings provide important insights into the role of spirituality in strengthening household economic resilience and provide input for Islamic financial institutions and policymakers in designing local value-based economic empowerment programs.